CALCULATION OF THE ENERGY SPECTRUM OF ELECTRONS USING THE KRONIG-PENNEY METHOD (Scientific journal of the Fergana State University, 2024)
In this article, the motion of electrons in crystals in a periodic potential field is analyzed using the Schrödinger equation. The Kronig-Penney method is used to determine the energy spectrum of electrons. According to this method, the atoms in the crystal lattice are represented by rectangular potential wells and barriers. Electrons exist only in allowed energy bands and cannot pass through forbidden bands. Additionally, the relationships between energy bands and forbidden bands are examined.